Potential Workers of the Impact of Covid-19 in the Informal Sector in the Era of the Industrial Revolution 4.0 in the City of Pekalongan - Triyono Triyono; Jumai Jumai; Edy Purwanto (Budapest International Research and Critics University, 2022)
The Indonesian government in facing the war against COVID-19 has taken various policies, one of which is the Implementation of Community Activity Restrictions (PPKM), this PPKM suppresses household activities and company productivity in the form of restrictions on community movement and company operations, resulting in a decrease in household and company consumption, a decrease in income business and a decrease in the demand for labor. The tangible form that can be seen from the impact of covid on the economy that can be seen today is the incident termination of employment (PHK). The purpose of this research is to mknow the conditions and potential of workers affected by termination of employment (PHK). In the informal sector in Pekalongan City in the Industrial Revolution 4.0 era. The research method used is a qualitative descriptive research type, with data sources obtained from informants, namely workers affected by layoffs and in the data analysis process, several stages are carried out, namely data collection, data reduction, data presentation and verification. The results of the study state that every worker who is laid off must survive in the midst of the covid-19 pandemic by utilizing their potential by utilizing assistance from the Government and other organizations or institutions for mastery and use of technology and the internet such as social media, marketplace, dropshipper, trading, youtuber, online motorcycle taxis, partners in go food.